STUDENTS’ ENGAGEMENT IN SOCIAL NETWORKING SITES AND ITS RELATION TO THEIR MASTERY OF CERTAIN ENGLISH FIXED EXPRESSIONS AND IDIOMS - Bambang Pramono; Machdalena Vianty; Fiftinova Fiftinova (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The objectives of the study were to find out to what extent the undergraduate students’ engagement in social networking sites and their mastery of certain English fixed expressions and idioms. This study also investigated whether or not there was a significant correlation between the students’ engagement in social networking sites and their mastery of certain English fixed expressions and idioms. One hundred and six undergraduate students of English Education Study Program of Teacher Training and Education Faculty of Sriwijaya University (Palembang Campus) were involved as population and sample of the study. A social networking sites engagement questionnaire and English fixed expressions and idioms test were used to collect the data which were statistically analized by using correlation and regression analyses. The result revealed students’ engagement on social networking sites level was very high with 82% average agreement questionnaire responses, but their mastery of certain English fixed expressions and idioms was low (60.47) with 79.2% students scored below 71. Next, the correlation between the students’ engagement in social networking sites and their mastery of certain English fixed expressions and idioms was positive and significant (r=0.328>0.249, p-value=0.001<0.05). The finding also showed students’ engagement in social networking sites contributed 10.8% to their mastery of certain English fixed expressions and idioms. In conclusion, the students have a very high level of engagement in social networking sites, but low level of mastery of certain English fixed expression and idioms. Keywords: engagement in social networking sites, proficiency in English fixed expressions and idioms, EFL students